2000
DOI: 10.1111/1467-971x.00153
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic Power in Virtual Communities: the Ebonics Debate on the Internet

Abstract: The recent controversy over the issue of Ebonics has been well documented in both the print media and in the electronic media, in particular, on the internet. The impact of electronic discourse has been the focus of a number of researchers (Birkerts, 1998;Lakoff, 1998;Vitanza, 1999). However, the locus of research of most theorists has been on the metalanguage of this discourse genre, and on its role in the creation of unique discourse communities (Foertsch, 1995;Hawisher and Moran, 1993). Few studies have exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…As a result of the pervasiveness of online communication, electronic discourses have been playing an essential role in the restructuring of knowledge across different communities (Pandey, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…As a result of the pervasiveness of online communication, electronic discourses have been playing an essential role in the restructuring of knowledge across different communities (Pandey, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…This study is based on the premise that with the rise of online communication, discourses found on websites and in other electronic media are playing an increasing role in knowledge construction across society (Pandey, ). Consequently, for the last few decades, linguists such as Fairclough (), Gee (), Gruber (), and Kress and Van Leeuwen () have turned their attention to the way electronic discourses play a role in shaping individuals' understanding of the world around them.…”
Section: Methodsmentioning
confidence: 99%
“…The journal World Englishes has previously published several articles related to the Internet and computer‐mediated communication including Pandey (, the Ebonics debate on an electronic bulletin board); Dimova (, computer‐related English loanwords on Macedonian business websites); Hardy and Friginal (, Filipino and American opinion columns and blogs); Troyer (, English in Thai online newspapers); Zhang (, multilingual creativity in Chinese microblogging); Ai and You (, syntactic features of English on an online discussion forum); Daud and Mclellan (, linguistic choices in Bruneian Facebook status updates); and Ong (, Singlish textese in multiparty chats). However, more contemporary social media platforms such as Facebook, Instagram, Twitter, and YouTube are hardly discussed as a main topic in the journal.…”
Section: Scope Of Special Issue On World Englishes and Digital Mediamentioning
confidence: 99%